Cut-Section Modules to Enhance the learning of Automotive Electronic Course - Mane, Venkatesh; Nissimagoudar, P. C.; Gireesha, H. M.; Iyer, Nalini C. (Journal of Engineering Education Transformations, 2018)
Automotive industry has grown significantly in the recent years and the expectations froman undergraduate are peaking up day by day.The automotive industry giants like Robert Bosch, KPIT, Mercedes Benz want industry ready graduates to put them on the project directly without spending much time on the OJTs(on job trainings). This would greatly reduce the time to market their products. The automotive industry is looking for the skilled engineers having strong knowledge of Automotive Systems along with electronics background. To address the industry needs stated above, at a institute level every student undergo automotive electronics theory course as a part of the curriculum during sixth semester but this does not completely fills the gap because students of electrical stream students have very little knowledge of automotive subsystem except very few basic parts but if students of electrical science has to apply electronics or build any system, they should have thorough knowledge of mechanical parts of the automotive systems. In order to fulfil this gap students are exposed to cut section modules in the automotive electronics lab and this exposure definitely helped the students in understanding and enhances the learning of the automotive electronics course.This indirectly boosted the placement count.